Examining the Role of Corporate Social Responsibility in Resident Attitude Formation: A Missing Link?. (September 2019) - Li, Xiang (Robert); Wang, Yuan; Zhang, Yingsha; Cao, Yang
Resident attitude toward the development of individual commercial tourism projects (e.g., theme parks and resorts) has not been well analyzed in tourism literature. In this study, the authors explored the role of corporate social responsibility (CSR) in understanding residents' attitudes toward a high-profile tourism project in its initial building stage. Four models were proposed to evaluate the role of CSR in resident attitude formation. Model comparison results suggest that the moderation model (i.e., CSR moderates the effect of perceived impacts on resident attitude) appears to be statistically and conceptually sound. The results reveal that CSR positively affects resident attitude and enhances the effect of environmental tourism impacts on resident attitude at the city level. Theoretical and empirical implications are discussed.